Analisis Penerapan Pedoman Asistensi Akuntansi Keuangan Desa dalam Mewujudkan Akuntabilitas dan Transparansi Dana Desa Dalam Perspektif Ekonomi Islam : (Studi Kasus Desa Nogo Rejo Kecamatan Galang Kabupaten Deli Serdang) - Putri Aulia Br Siregar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the application of village financial accounting assistance guidelines in realizing accountability and transparency of village funds in NogoRejo Village, Galang District, Deli Serdang Regency and what the Islamic economic view of accountability and transparency is. Accountability and Transparency are important elements that cannot be separated, a good and accountable financial report will produce a good transparent financial report as well, so these two elements are very important in managing funds, both central government funds, provincial governments, district governments /city, or village government. The method used in this research is a field study which includes observation, interviews and documentation. This research uses qualitative methods, and the data analysis technique used is descriptive analysis. The results of this research show that the village accounting assistance guidelines implemented by NogoRejo Village have played a role in accountability and transparency in managing village funds. However, the guidelines will not be implemented if village officials do not first understand the existing guidelines. In carrying out responsibility (accountability) for managing village funds in NogoRejo Village, based on each process carried out by village officials in accordance with the guidelines set by the Minister of Home Affairs and village officials who have carried out their duties in their respective fields, all funds that have been allocated for activities will be made into information boards.